(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Document classification is a means of knowledge extraction in text mining process. This has been experimented by so many researches. But still we have included one of the extra features in the preprocessing phase and checked its outcome with Support Vector Machine (SVM). The feature selection has been accounted with the Vector space method, Single Value Decomposition (SVD) which is specifically meant for dimension reduction. The experiment has shown some positive changes in classification Â Keywords: Document classification â€“ Support Vector Machine â€“ Singular Value Decomposition